THE IMPACT OF POLITICAL INTELLIGENCE ON MANAGERS POLITICAL BEHAVIOR (CASE STUDY: MUNICIPALITIES OF KHORASAN RAZAVI PROVINCE) - Hamouni, Seyed; Lari, Masoud; Bahramzadeh, Hosein (Revista Inclusiones, 2019)
This study aimed at investigating the effect of political intelligence on political behavior of managers. It was an applied mixed method research. The statistical population included the managers of municipality of Khorasan Razavi province in February of 2016 (N=366) in 73 cities. The sample size was calculated using Cochran formula (N=191). Stratified random sampling was used according to the statistical population. A researcher-made questionnaire was used to collect data. Validity of the questionnaire was verified through Cronbach alpha which was greater than 0.7. Descriptive and inferential statistics were used to analyze the data. Structural equation modelling and the IBM SPSS 21 and IBM AMOS version 3 software were used. The findings showed that political intelligence affects the political behavior of managers by 0.84. Thus, by improving the political intelligence of managers, one can predict 84% of managers’ political behavior.